CHANGING ORGANIZATIONAL BEHAVIOR THROUGH HIS DIMENSIONS - Jorovlea, Elvira (SWorldJournal, 2023)
Organizational behavior is the study of the behavior of individuals in organizations, which involves the understanding, prediction and control of human behavior, models and structures, with the aim of improving the environment, performance and efficiency